WELCOMING THE DIGITAL ERA: TECHNOLOGICAL INNOVATION IN TAX ADMINISTRATION - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
This article discusses the application of technological innovation in tax administration in the digital era. Digital transformation has brought significant changes that improve operational efficiency, data accuracy, and ease of access and transparency of information in the tax system. Technologies such as Big Data, artificial intelligence (AI), and blockchain play an important role in optimising the tax collection process and minimising tax evasion. However, behind these opportunities, there are challenges such as data security, digital divide, and resistance to change that need to be overcome. Collaboration between the government, private sector, and society is essential to create an ecosystem that supports this digital transformation. In conclusion, technological innovation in tax administration is not just an option, but an urgent need to improve the efficiency, effectiveness, and contribution of the tax sector to sustainable and equitable economic development.